Utilizing Mind Mapping to Summarize English Text with the Theme "American Culture" - Vivi Aulia (Journal of Educational Science and Technology (EST), 2017)
This research aims at knowing and describing on the utilization of mind mapping strategy in summarizing English text under the theme American Culture. It is conducted to the third semester of English Department students at STKIP PGRI Banjarmasin batch 2016 who take Reading III course. The instruments used in this research are observation sheet and documentation of students’ mind map products. The observation sheet is analyzed qualitatively by describing the important result of observation process while the students’ mind maps are analyzed quantitatively using mind mapping scoring rubric. They create mind mapping in post-reading activity. After reading, they have to summarize the text written through mind map. The result from the observation sheet shows that during four meetings of learning to create mind maps, students carry out the steps of creating mind map well. Although they get difficulties in early activities of this process, however, they can accomplish it well in the last meeting with a different topic of the text. Moreover, there are 17 (51%) of 33 students as the subject of this research who have a good score on their mind maps products. It indicates that utilizing mind map is good enough for helping them to summarize the text written.